Religiosity and patterns of alcohol consumption among users of primary healthcare facilities in Brazil - Edson Zangiacomi Martinez; Anderson Soares da Silva; Flávia Masili Giglio; Natalia Akemi Yamada Terada; Miriane Lucindo Zucoloto (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2019)
Abstract Background A number of studies have been reported on the role of religiosity in health beliefs and behaviors. Objective The objective of this cross-sectional study is to examine the association between religious involvement and patterns of alcohol consumption in a large representative sample of users of primary healthcare facilities in Ribeirão Preto, Southeast Brazil. Method Data were collected through personal interviews. Religiosity was measured using the Duke University Religion Index (DUREL) and the alcohol consumption was measured using the Alcohol Use Disorders Identification Test (AUDIT) questionnaire. Multinomial logistic regression models were used to evaluate the associations between the participant characteristics, the AUDIT risk levels, and the drinking groups. Results The sample was composed of 841 women with a mean age of 39.5 years old and 214 men with a mean age of 45.1 years old. A significant relationship between patterns of alcohol consumption and the multiple dimensions of religiosity was detected, such as religious affiliation, religious practices, self-perception of the level of religiosity and the ORA, NORA and IR components of DUREL. Lower levels of drinking risk were detected among religious individuals and among those who practice their religions compared to individuals who have no religion and/or non-practicing individuals, respectively. Conclusion A lifestyle motivated by religious concerns is associated with alcohol use habits among the Brazilian users of the public healthcare facilities.